Growth and interfacial structure of methylammonium lead iodide thin films on Au(111) - She, Limin; Liu, Meizhuang; Li, Xiaoli; Cai, Zeying; Zhong, Dingyong (Surface science, 2017)
Due to the promising optoelectronic properties, organic-inorganic hybrid perovskites have been intensively studied as the active layers in perovskite solar cells. However, the structural information about their interface, one of the key factors determining device performances, is so far very rare. Herein, we report on the growth of CH3NH3PbI3 (MAPbI3, MA=CH3NH3) thin films by means of vapor deposition under ultrahigh vacuum. The surface morphology and interfacial structure have been investigated by scanning tunneling microscopy. At the initial growth stage, a complicated transient phase consisting of three atomic layers, i.e., iodine, MA-PbI4 and MA-I, was formed on the Au(111) substrate. With the coverage increasing, atomically smooth MAPbI3 films with orthorhombic structure have been obtained after annealing to 373K. The films followed a self-organized twofold-layer by twofold-layer growth mode with the formation of complete PbI6 octahedrons and the exposure of MA-I terminated (001) surface. [Display omitted] •This is the first work unveiling the growth and the interfacial structures of hybrid perovskites at the atomic scale.•At the initial stage, a complicated transient phase consisting of iodine, MA-PbI4 and MA-I layer was firstly formed on the Au(111) substrate.•With the coverage increasing, the high-quality CH3NH3PbI3 films were grown by the stacking of PbI2-MAI twofold layers.•Annealing at a proper annealing temperature (373K) can improve the domain size and efficiently reduce the defect density.